Role of shielding gas in tailoring microstructure and anisotropy in wire arc additive manufactured Inconel 686 - S. Ajithkumar; B. Arulmurugan; M. Manikandan; M. Sathishkumar (Scientific Reports)
Abstract This study examines the effect of shielding gas composition on the microstructure and mechanical properties of Inconel 686 components fabricated via wire arc additive manufacturing (WAAM). Thin-walled structures were produced using pure Argon (Ar), a 50% Helium-Argon mixture (Ar + 50% He), and pure Helium (He). Cooling rates were highest with pure He and lowest with pure Ar. Microstructural analysis revealed variations in dendritic structures, with pure He producing the finest cellular and equiaxed structures. X-ray diffraction (XRD) confirmed that the pure He sample had the smallest crystallite size (24.4 nm) and the highest dislocation density (16.8 × 10⁻⁴ nm⁻²) due to rapid cooling. Energy dispersive X-ray spectroscopy (EDS) showed that Mo-rich segregation was most pronounced in pure Ar, reduced in Ar + 50% He, and minimal in pure He due to finer grain refinement. The pure He sample also exhibited the highest microhardness, tensile strength, and yield strength while reducing anisotropy, outperforming both the Ar + 50% He and pure Ar samples.